2011
DOI: 10.3233/ao-2011-0083
|View full text |Cite
|
Sign up to set email alerts
|

Creating the ontologists of the future

Abstract: The goal of the Ontology Summit 2010 was to address the current shortage of persons with ontology expertise by developing a strategy for the education of ontologists. To achieve this goal we studied how ontologists are currently trained, the requirements identified by organizations that hire ontologists, and developments that might impact the training of ontologists in the future. We developed recommendations for the body of knowledge that should be taught and the skills that should be developed by future onto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…During the Ontology Summit 2010, leading ontology experts discussed the training and education of future ontologists. In the resulting document the authors identify core knowledge and core skills that are required for an ontologist to be able to develop ontologies successfully (Neuhaus et al, 2011). Of the 15 core skills that were identified, 14 are technical (e.g., the ability to conduct an ontological analysis or choose an appropriate representation language).…”
Section: Implications For the Training (And Hiring) Of Ontologistsmentioning
confidence: 99%
“…During the Ontology Summit 2010, leading ontology experts discussed the training and education of future ontologists. In the resulting document the authors identify core knowledge and core skills that are required for an ontologist to be able to develop ontologies successfully (Neuhaus et al, 2011). Of the 15 core skills that were identified, 14 are technical (e.g., the ability to conduct an ontological analysis or choose an appropriate representation language).…”
Section: Implications For the Training (And Hiring) Of Ontologistsmentioning
confidence: 99%
“…Domain ontologies can describe a domain of learning in terms of its composition of concepts, the connections between concepts and the further semantic differentiation of the concepts and connections. Domain ontologies are created and maintained by ontology engineers who translate expert knowledge into the representation of the ontology (Neuhaus et al , 2011). In doing so, the knowledge is codified into the composition and connections of the concepts, as well as into the description of the semantics of concepts and connections.…”
Section: Connection-aware Semantic Learning Servicesmentioning
confidence: 99%
“…Paralleling this strong interest there is a flourishing growth of courses in academia and professional institutions; however, these courses are often single courses within larger programs. The authors in (Neuhaus, 2011) identified only one complete academic program completely devoted to education in applied ontology (a Master's program at the University of Buffalo) and 21 programs that offer ontology-centered topics.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to give a detailed overview of the curriculum taught in a Master's-level class in Informatics Engineering in order to "describe in more detail" how some of the knowledge and skills indicated in (Neuhaus, 2011) can be acquired. Our curriculum is "IT-oriented" with a particular emphasis placed on the knowledge and deployment of "IT systems involving many components in addition to the ontology itself" (Neuhaus, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation